Estimulación cognitiva en el proceso de lectoescritura para estudiantes con discapacidad intelectual de educación básica elemental - Quimi Quimi, Janeth Margarita (2021)
Cognitive stimulation plays a determining role during the childhood stage, since it contributes to improving evolutionary development; The more a child can have stimulating experiences, the more synapses he will create in his brain and consequently his brain development can be fuller. In those with an intellectual disability, this becomes even more necessary, since, if they act from an early age, they will be able to achieve a higher level of autonomy and independence in various areas and contexts……..